EFEKTIFITAS WAKTU TUNGGU DAN LOKASI TERHADAP KEPUASAN PELANGGAN - Amna Mawardi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This research was conducted to find out what factors can influence consumers satisfaction. In this study used two independent variables Waiting Time (X1), and Location (X2), while Customer Satisfaction (Y) as the dependent variable. After reviewing the literature and formulating hypotheses, data collection was carried out by distributing questionnaires to 97 consumers at Gemah Ripah Purwakarta Restaurant who had carried out the purchase using non probility sampling techniques. For analysis and elaboration of data using SPSS version 21. Then there are several tests performed in analyzing data, such as measuring instruments, classical assumption tests, multiple linear regression analysis and hypothesis testing. Based on the results of the analysis found that the two independent variables have a significant and positive effect on the dependent variable. Waiting time variable has a positive effect of 0.488 with a significance level of 0,000. Location variables have a positive effect of 0.566 with a significance level of 0.000. Adjusted R Square of the three variables is 0.662 or 66.2% which means that the two variables are able to explain the variation in the dependent variable of 66.2 percent with 33.8 percent explained by other variables not used in this study.